Short term outcomes of the first pediatric cardiac surgery program in Rwanda - Yayehyirad Ejigu; Vongai C. Mlambo; Kara L. Neil; Habtamu Sime; Rex Wong; Michel R. Gatera; Gaston Nyirigira; Yilkal C. Sewnet; Yihan Lin; Bertrand Byishimo; Gloria Rukomeza; Yves Mutabandama; et al. (Journal of Cardiothoracic Surgery)
Abstract Background While the number of cardiac surgery programs in sub-Saharan Africa are increasing, it is still insufficient. With only 0.08 pediatric cardiac surgeons per million people, few cardiac centers routinely perform pediatric cardiac surgery. This has led to reliance on humanitarian medical missions or referral abroad for most African nations. This study outlines the outcomes of Rwanda’s first sustainable pediatric cardiac surgery program. Methods A retrospective chart review was performed for all pediatric patients who received cardiac surgery between October 2022 and April 2024. Patient demographics, procedures, operative times, length of stay, complications, and 30-day mortality were synthesized. Perioperative factors associated with complications and prolonged intensive care unit length of stay were evaluated using logistic and linear regression analysis, respectively. Results 207 patients received 240 cardiac procedures. At time of surgery, 45% of patients were 1–5 years old (n = 95). The top five procedures were repair of Ventricular Septal Defect, Patent Ductus Arteriosus, Atrial Septal Defect, Tetralogy of Fallot and Coarctation of the Aorta. 30-day mortality was 1.9% (n = 4) and 6.3% (n = 13) experienced a major complication. Additionally, 24% (n = 50) experienced minor complications, most commonly, pneumonia. The linear combination of surgery duration, cross clamp and bypass time was significantly associated with having complications (aOR = 0.67, p = 0.01). Younger age, longer operative times, number of inotropes and the presence of complications were associated with an increased intensive care unit stay. Conclusions The 30-day surgical outcomes are favorable compared to programs with a similar case mix, showing that pediatric cardiac surgery can be safely performed in developing countries with local cardiac teams. Prolonged bypass and cross clamp times were associated with higher complication rates and increased inotrope use was associated with longer intensive care unit stay.